Green synthesis of lead oxide nanoparticles for photo-electrocatalytic and antimicrobial applications - Khan, Zia Ul Haq; Gul, Noor Shad; Mehmood, Faisal; Sabahat, Sana; Muhammad, Nawshad; Rahim, Abdur; Iqbal, Jibran; Khasim, Syed; Salam, Mohamed Abdel; Khan, Taj Malook; Wu, Jianbo (Frontiers in Chemistry, 2023)
Synthesis of nanoparticles (NPs) for many different uses requires the development of environmentally friendly synthesis protocols. In this article, we present a simple and environmentally friendly method to synthesize lead oxide (PbO) NPs from the plant material of the Mangifera indica. Analytical techniques such as spectroscopy, X-ray diffraction, and microscopy were used to characterize the synthesized PbO NPs, and their photo-electrocatalytic and antifungal properties were also evaluated. H2O2 was used to investigate the efficacy of removing methylene blue dye. At a range of pH values, H2O2 was used to study the role of hydroxyl radicals in the breakdown of methylene blue dye. Methylene blue dyes are more easily eliminated due to increased generation of the *OH radical during removal. Dye extraction was also significantly affected by the aqueous medium's pH. Additionally, the electrocatalytic properties of the PbO NPs adapted electrode were studied in CH3COONa aqueous solution using cyclic voltammetry. Excellent electrocatalytic properties of the PbO NPs are shown by the unity of the anodic and cathodic peaks of the modified electrode in comparison to the stranded electrode. Aspergillus flavus, Aspergillus niger, and Candida glabrata were some fungi tested with the PbO NPs. Against A. flavus (40%) and A. niger (50%), and C. glabrata (75%), the PbO NPs display an excellent inhibition zone. Finally, PbO NPs were used in antioxidant studies with the powerful antioxidant 2, 2 diphenyl-1-picrylhydrazyl (DPPH). This study presents a simple and environmentally friendly method for synthesizing PbO NPs with multiple useful properties, including photo-electrocatalytic and antimicrobial activity.